Synergistic and sustainable utilization of coconut shell ash and groundnut shell ash in ternary blended concrete - Bheel, N. (Springer Science and Business Media Deutschland GmbH, 2022)
The quest for eco-sustainable binders like agro-wastes in concrete to reduce the carbon footprint caused by cement production has been ongoing among researchers recently. The application of agro-waste-based cementitious materials in binary concrete has been said to improve concrete performance lately. Coconut and groundnut shells are available in abundant quantities and disposed of as waste in many world regions. Therefore, the use of coconut shell ash (CSA) and groundnut shell ash (GSA) in a ternary blend provides synergistic benefits with Portland cement (PC) and may be sustainably utilized in concrete as ternary cementitious material (TCM). Therefore, this study presents concrete performance with CSA and GSA in a grade 30 ternary concrete. Two hundred ten numbers of standard concrete samples were cast for checking the fresh and mechanical properties of concrete at curing ages of 7, 28, and 90 days. After 28-day curing, the experimental results show an increment in compressive, tensile, and flexural strength by 11.62, 8.39, and 9.46 at 10 TCM cement replacement, respectively. The concrete density and permeability coefficient reduce as TCMâs content increases. The modulus of elasticity after 90 days improved with the addition of TCM. The concreteâs sustainability assessment indicated that the emitted carbon for concrete decreased by around 16 using 20 TCM in concrete. However, the workability of fresh concrete declines as TCM content increases. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.